Solid hydrogen storage material based on magnesium foil coating and preparation method thereof
By using a micron-scale magnesium foil plating catalyst film system and high vacuum magnetron sputtering technology in magnesium-based solid hydrogen storage materials, combined with external magnetic field treatment, the existing magnesium-based solid hydrogen storage materials have solved the problem of high hydrogen storage temperature and slow dehydrogenation rate, and achieved better hydrogen absorption and discharge performance.
Patent Information
- Application Number
- CN202510009310.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-04-11
AI Technical Summary
The existing magnesium-based solid hydrogen storage materials have a high hydrogen storage temperature and a slow dehydrogenation rate, making it difficult to achieve hydrogen absorption at room temperature.
A micron-scale magnesium foil plating catalyst film system was used to prepare a solid hydrogen storage material of LaNi5 magnesium foil plated by high vacuum magnetron sputtering technology, and magnetization was carried out under an external magnetic field to improve the hydrogen absorption and discharge performance.
A lower hydrogen storage and discharge temperature and faster hydrogen storage and discharge kinetics are achieved. The LaNi5 solid hydrogen storage material with magnesium foil can start to absorb hydrogen at a pressure of 3.5 bar, and hydrogen discharge at a pressure of 28.2 bar, which significantly improves the hydrogen absorption and discharge kinetics of pure magnesium.
Smart Images

Figure CN119800307A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of hydrogen storage materials, and more particularly to a solid hydrogen storage material based on magnesium foil coating and a preparation method thereof. Background Art
[0002] Energy is an important material support for a country's development, involving multiple aspects such as economy, politics, and military security. With the proposal and implementation of the country's "dual carbon" goals, energy development with new energy as the main force has made rapid progress, especially hydrogen energy, which is considered to be one of the most promising energy sources to replace fossil fuels due to its unique physical and chemical properties.
[0003] However, hydrogen storage and transportation has become the main bottleneck problem faced by the current hydrogen energy supply chain. Developing safe and efficient hydrogen storage and transportation methods is a key link in achieving efficient application of hydrogen energy. Common hydrogen storage methods include gaseous hydrogen storage, liquid hydrogen storage and solid hydrogen storage. Gaseous hydrogen storage has a low volume hydrogen storage density and poses a safety hazard. Liquid hydrogen storage has a high cost and is easy to volatilize. Solid-state hydrogen storage has a higher volume hydrogen storage density and mass hydrogen storage density, and has the advantages of good safety. It has gradually developed into one of the ideal hydrogen storage methods. Among them, MgH2 solid-state hydrogen storage has a higher theoretical hydrogen storage density and good reversible cyclicity, and Mg also has the advantages of abundant reserves and low cost. However, its hydrogen absorption and desorption reactions have great obstacles in both thermodynamics and kinetics. In view of this, researchers in this field have modified and adjusted MgH2 through nano-sizing, alloying, and catalyst doping.
[0004] Catalysis is an effective method to improve the kinetics of hydrogen absorption and desorption of MgH2. Adding catalysts can promote the dissociation of hydrogen, accelerate the rate of hydrogen absorption and desorption, and form more active sites for MgH2 nucleation. Common catalysts include metals, metal oxides, nanocarbon materials, etc. Although adding catalysts improves the hydrogen absorption and desorption performance of MgH2 to a certain extent, it still has the problem of too high hydrogen absorption and desorption temperature and unclear mechanism of the catalytic process, and it is still difficult to achieve hydrogen absorption at room temperature.
[0005] Relevant literature shows that the current modification methods for magnesium-based solid-state hydrogen storage in this field are generally ball milling, smelting, or nano-sizing of Mg and metal catalysts, but the effect of improving hydrogen storage performance is unsatisfactory. The film has a large specific surface area, fast kinetics, slow pulverization speed, and can achieve nano-level precise control.
[0006] Therefore, the present invention proposes a solid-state hydrogen storage material based on magnesium foil coating and a preparation method thereof, and adopts a micron-level magnesium foil-coated catalyst membrane system to achieve lower hydrogen storage and desorption temperature and faster hydrogen storage and desorption kinetics. Summary of the invention
[0007] The purpose of the present invention is to propose a LaNi5 solid hydrogen storage material based on magnesium foil to address the shortcomings of the existing magnesium-based solid hydrogen storage powder material, such as complicated preparation process, high hydrogen storage and desorption temperature, and slow dehydrogenation rate. The hydrogen storage material can absorb hydrogen at low pressure, and has better dehydrogenation kinetics than pure magnesium;
[0008] Another object of the present invention is to provide a method for preparing solid-state hydrogen storage materials based on magnesium foil coating, which achieves the goals of rapid kinetics and cyclic characteristics by controlling sputtering power, substrate temperature, film type and quantity, and applying an external magnetic field strength to the coated product.
[0009] In order to achieve the above object, the present invention adopts the following technical solution:
[0010] A method for preparing a solid hydrogen storage material based on magnesium foil coating comprises the following steps:
[0011] (1) The Pd target and the catalyst target are mounted on the radio frequency target position of a high vacuum magnetron sputtering instrument, and the magnesium foil with a surface polished and deoxidized is used as a substrate and mounted on a rotating base in the chamber of the magnetron sputtering instrument;
[0012] (2) Evacuate the cavity of the magnetron sputtering instrument and introduce a protective atmosphere;
[0013] (3) After all parameters in the magnetron sputtering instrument are stable, pre-sputtering is performed on the catalyst target material LaNi5 to remove the oxide layer and contamination layer on the surface of the target material;
[0014] (4) performing rotational sputtering on the magnesium foil substrate, controlling the sputtering deposition power, base rotation speed, protective gas flow rate, target-substrate distance and angle so that the magnesium foil substrate passes over the catalyst LaNi5 target and Pd target, and obtaining a magnesium foil-plated LaNi5 solid hydrogen storage material after sputtering;
[0015] (5) The LaNi5 solid hydrogen storage material coated with magnesium foil is placed in a magnetizing device in a glove box for magnetization, and the strength of the external magnetic field is controlled.
[0016] Preferably, the protective atmosphere in step (2) is high-purity argon.
[0017] Preferably, in the magnesium foil-plated LaNi5 solid hydrogen storage material in step (4), the thickness ratio of the magnesium foil to the LaNi5 film is 100:1.
[0018] Preferably, in step (4), Pd is sputtered first and then LaNi5 is sputtered, the target-substrate distance of the Pd target is 130 mm, the angle is 20°, the sputtering deposition power is DC 50W-100W, and the sputtering time is 10s-60s.
[0019] Preferably, in step (4), the target-substrate distance of the LaNi5 target is 140 mm, the angle is 20°, the sputtering power is RF100W-200W, the sputtering time is 30-150min; and the base rotation speed is 3rpm-8rpm.
[0020] Preferably, the protective gas flow rate in step (4) is 30-40 sccm, and the working gas pressure is 0.4-0.5 Pa.
[0021] Preferably, the vacuum in step (2) is evacuated to 2.0×10 -5 Pa.
[0022] Preferably, the strength of the external magnetic field in step (5) is 0.15T.
[0023] Preferably, in step (5), the magnesium foil-plated LaNi5 solid hydrogen storage material needs to be ensured not to come into contact with air to prevent the magnesium-based material therein from being oxidized.
[0024] It can be seen from the above technical solution that compared with the prior art, the present invention has the following beneficial effects:
[0025] (1) The preparation method of the magnesium foil plated LaNi5 solid hydrogen storage material of the present invention has a simple preparation process, simple operation, and low raw material price;
[0026] (2) The preparation method of the solid hydrogen storage material of magnesium foil coated with LaNi5 of the present invention can change the hydrogen absorption and dehydrogenation kinetics of LaNi5 by adjusting the magnetic field intensity, thereby changing the hydrogen absorption and dehydrogenation performance of the overall material; at the same time, nano-scale regulation of catalyst film layers of different thicknesses can be achieved by adjusting the magnetron sputtering parameters, power, etc.;
[0027] (3) The magnesium foil coated LaNi5 solid hydrogen storage material obtained by the preparation method of the magnesium foil coated solid hydrogen storage material of the present invention has excellent hydrogen absorption and desorption performance. The hydrogen storage material can start to absorb hydrogen at a pressure of 3.5 bar and start to desorb hydrogen at a pressure of 28.2 bar. It has good hydrogen absorption and desorption kinetics, which is significantly improved compared with the hydrogen absorption and desorption kinetics of pure Mg. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0029] Figure 1 is the PCT adsorption kinetic curve in Example 1 of the present invention;
[0030] Figure 2 This is the PCT adsorption kinetics curve in Comparative Example 1 of the present invention;
[0031] Figure 3 This is a SEM characterization result diagram of the product of Example 1 of the present invention. DETAILED DESCRIPTION
[0032] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] Example 1
[0034] This embodiment provides a method for preparing a solid hydrogen storage material based on magnesium foil coating, comprising the following steps:
[0035] (1) Pd target and catalyst target LaNi5 are mounted on the radio frequency target position of a high vacuum magnetron sputtering instrument, and a magnesium foil with a polished and deoxidized surface is used as a substrate and mounted on a rotating base in the chamber of the magnetron sputtering instrument;
[0036] (2) Evacuate the cavity of the magnetron sputtering instrument and introduce a protective atmosphere;
[0037] (3) After the power and other parameters of the magnetron sputtering instrument are stable, the catalyst target is pre-sputtered to remove the oxide layer and contamination layer on the surface of the target;
[0038] (4) performing rotational sputtering on the magnesium foil substrate, controlling different sputtering powers, base rotation speed, protective gas flow rate, target-substrate distance and angle so that the magnesium foil substrate passes over the catalyst LaNi5 target and Pd target, and obtaining a magnesium foil-plated LaNi5 solid hydrogen storage material after sputtering;
[0039] (5) The packaged magnesium foil-coated LaNi5 solid hydrogen storage material was placed in a glove box, and then subjected to an external magnetic field strength of 0.15 T. The magnetized sample was taken out and placed in the BSD-PH (PCT hydrogen storage adsorption instrument) for relevant tests.
[0040] In this embodiment, the sputtering power of the Pd target is RF80W, and the sputtering power of the LaNi5 target is RF150W; the rotation speed of the Pd target and the LaNi5 base is 5rpm, and the sputtering time is 80min; the protective atmosphere is high-purity argon gas, the protective atmosphere flow rate is 36sccm, the working gas pressure is 0.4pa, and the vacuum degree of the high vacuum magnetron sputtering equipment cavity is evacuated to 2.0×10 -5 Pa.
[0041] Comparative Example 1
[0042] The comparative example provides a method for preparing a solid hydrogen storage material, comprising the following steps:
[0043] (1) The Pd target is mounted on the radio frequency target position of a high vacuum magnetron sputtering instrument, and the magnesium foil with a polished and deoxidized surface is used as a substrate and mounted on a rotating base in the chamber of the magnetron sputtering instrument;
[0044] (2) Evacuate the cavity of the magnetron sputtering instrument and introduce a protective atmosphere;
[0045] (3) After the power and other parameters of the magnetron sputtering instrument are stable, the Pd target is pre-sputtered to remove the oxide layer and contamination layer on the surface of the target;
[0046] (4) performing rotational sputtering on the magnesium foil substrate, controlling different sputtering powers, base rotation speed, shielding gas flow rate, target-substrate distance and angle so that the magnesium foil substrate passes over the Pd target material, and obtaining a magnesium foil-coated Pd solid hydrogen storage material after sputtering;
[0047] (5) The packaged magnesium foil-plated Pd solid hydrogen storage material was placed in a glove box, and then an external magnetic field strength of 0.15 T was applied. The magnetized sample was taken out and placed in the BSD-PH (PCT hydrogen storage adsorption instrument).
[0048] In this comparative example, the sputtering power of the Pd target is RF120W; the substrate rotation speed is 5rpm, the sputtering time of Pd is 90min; the protective atmosphere is high-purity argon gas, the protective atmosphere flow rate is 30sccm, the working gas pressure is 0.5pa, and the vacuum degree of the high vacuum magnetron sputtering equipment cavity is evacuated to 2.0×10 -5 Pa.
[0049] Effect Experiment
[0050] The initial pressure of hydrogen absorption and desorption of the sample was tested using BSD-PH (PCT hydrogen storage adsorption instrument):
[0051] The method for testing the hydrogen storage capacity of the sample is as follows: select the PCT test on the instrument homepage, place about 150 mg of sample in the sample tube, evacuate the sample after installation, fill it with hydrogen at a pressure of 40 bar and set the temperature to 350°C in 20 minutes, then click Start Test.
[0052] The dehydrogenation temperature test method of the sample is: The sample dehydrogenation temperature test method is: Select TPD test on the instrument homepage, place about 150 mg of sample in the sample tube, evacuate the sample after installation, set the test temperature to 550 degrees Celsius, the test pressure to 0.01 bar, and click to start the test.
[0053] The results are shown in Table 1:
[0054] Table 1
[0055] Sample name Initial hydrogen absorption pressure / bar Initial dehydrogenation pressure / bar Example 1 3.5 28.2 Comparative Example 1 (pure magnesium) 8.5 11.3
[0056] Figure 1 Example 1 The initial hydrogen absorption pressure is 3.5 bar, and the initial dehydrogenation pressure is 28.2 bar;
[0057] Figure 2 In comparative example 1, the initial hydrogen absorption pressure was 8.5 bar, and the initial dehydrogenation pressure was 11.3 bar;
[0058] Comparing the two figures, the good sample can absorb hydrogen at a lower pressure, has better dehydrogenation kinetics, and the performance of Example 1 is better.
[0059] Figure 3 The SEM characterization results of the film surface of the product of the present invention are shown in the figure. It can be observed that the surface is uniform and the roughness is small.
[0060] In this specification, each embodiment is described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the embodiments can be referred to each other. For the device disclosed in the embodiment, since it corresponds to the method disclosed in the embodiment, the description is relatively simple, and the relevant parts can be referred to the method part.
[0061] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing a solid hydrogen storage material based on magnesium foil coating, characterized in that: The following steps are involved: (1) The Pd target and the catalyst target are mounted on the radio frequency target position of a high vacuum magnetron sputtering instrument, and the magnesium foil with a surface polished and deoxidized is used as a substrate and mounted on a rotating base in the chamber of the magnetron sputtering instrument; (2) Evacuate the cavity of the magnetron sputtering instrument and introduce a protective atmosphere; (3) After all parameters in the magnetron sputtering instrument are stable, pre-sputtering is performed on the catalyst target material LaNi5; (4) performing rotational sputtering on the magnesium foil substrate, controlling the sputtering deposition power, base rotation speed, protective gas flow rate, target-substrate distance and angle so that the magnesium foil substrate passes over the catalyst LaNi5 target and Pd target, and obtaining a magnesium foil-plated LaNi5 solid hydrogen storage material after sputtering; (5) The magnesium foil-coated LaNi5 solid hydrogen storage material is placed in a magnetizing device in a glove box for magnetization, and the strength of the external magnetic field is controlled.
2. The method for preparing a solid hydrogen storage material based on magnesium foil coating according to claim 1, characterized in that: The protective atmosphere in step (2) is high-purity argon.
3. The method for preparing a solid hydrogen storage material based on magnesium foil coating according to claim 1, characterized in that: In the magnesium foil-coated LaNi5 solid hydrogen storage material described in step (4), the thickness ratio of the magnesium foil to the LaNi5 film is 100:
1.
4. The method for preparing a solid hydrogen storage material based on magnesium foil coating according to claim 1, characterized in that: In step (4), Pd is sputtered first and then LaNi5 is sputtered. The target-substrate distance of the Pd target is 130 mm, the angle is 20°, the sputtering deposition power is DC 50W-100W, and the sputtering time is 10s-60s.
5. The method for preparing a solid hydrogen storage material based on magnesium foil coating according to claim 1, characterized in that: In step (4), the target-substrate distance of the LaNi5 target is 140 mm, the angle is 20°, the sputtering power is RF100W-200W, the sputtering time is 30-150min; and the base rotation speed is 3rpm-8rpm.
6. The method for preparing a solid hydrogen storage material based on magnesium foil coating according to claim 1, characterized in that: The protective gas flow rate in step (4) is 30-40 sccm, and the working gas pressure is 0.4-0.5 Pa.
7. The method for preparing a solid hydrogen storage material based on magnesium foil coating according to claim 1, characterized in that: The vacuum was evacuated to 2.0×10 -5 Pa.
8. The method for preparing a solid hydrogen storage material based on magnesium foil coating according to claim 1, characterized in that: The intensity of the external magnetic field in step (5) is 0.15T.
9. A solid hydrogen storage material based on magnesium foil coating, characterized in that: The solid-state hydrogen storage material is prepared by the method for preparing the solid-state hydrogen storage material based on magnesium foil coating according to any one of claims 1 to 8.
Citation Information
Patent Citations
Preparation method of LaNi5 film and application thereof
CN102220560A
Method for preparing AB5 type hydrogen storage alloy by rapid quenching of melt under action of magnetic field
CN102534276A
Making method of oxygen-storaged alloy film
CN1062770A
Magnesium-based ternary hydrogen storage alloy film and preparation method thereof
CN116240494A
Hydrogen occluding laminated structure
JP2002105576A